RESEARCH OF THE TRANSPARENCY CHARACTERISTICS OF THE ATMOSPHERE WHICH INFLUENCE THE FLIGHT CONTROL OF FLYING MACHINES: RESEARCH OF THE TRANSPARENCY CHARACTERISTICS OF THE ATMOSPHERE WHICH INFLUENCE THE FLIGHT CONTROL OF FLYING MACHINES - Getzov, Petar; Stoyanov, Stiliyan; Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A detailed optical research is carried about to examine the transparency characteristics out of the atmosphere which influence the flight control of self-moving and self-indicating flying machines. Methods for determining the atmosphere transparency coefficient for monochrome and compound radiation are proposed. The water vapours quantity in horizontal and vertical direction is calculated. Methods for determining the mass of the air and the carbon gas in horizontal, included and vertical direction are proposed.